Concomitant use of an immunomodulator with ustekinumab as an induction therapy for Crohn's disease: A systematic review and meta‐analysis. Issue 7 (3rd February 2021) - Yoshihara, Takeo; Shinzaki, Shinichiro; Amano, Takahiro; Iijima, Hideki; Takehara, Tetsuo; Inoue, Nagamu; Uchino, Motoi; Esaki, Motohiro; Kobayashi, Taku; Saruta, Masayuki; Sugimoto, Ken; Nakamura, Shiro; et al.
Abstract: Background and aim: Ustekinumab (UST), a fully humanized monoclonal antibody against the p40 subunit of interleukin‐12/23, is effective for the treatment of Crohn's disease (CD). The benefit of concomitant use of an immunomodulator (IM) with UST, however, is unclear. This study aimed to provide a systematic review and meta‐analysis comparing the efficacy and safety of concomitant use of an IM with UST as an induction therapy for CD patients. Methods: A systematic literature search was performed using PubMed/MEDLINE, the Cochrane Library, and the Japana Centra Revuo Medicina from inception to October 31, 2019. The main outcome measure was achievement of clinical efficacy (remission, response, and clinical benefit) at 6–12 weeks. The quality of the included studies was assessed using the risk of bias in non‐randomized studies of interventions (ROBINS‐I) tools. The fixed‐effects model was used to calculate the pooled odds ratios. Results: From 189 yielded articles, six including a total of 1507 patients were considered in this meta‐analysis. Concomitant use of an IM with UST was significantly effective than UST monotherapy as an induction therapy (pooled odds ratio in the fixed‐effects model: 1.35, 95% confidence interval [1.06–1.71], P  = 0.015). The heterogeneity among studies was low ( I 2  = 2.6%). No statistical comparisons of the occurrence of adverse events between UST monotherapy and concomitant use of an IM with UST were performed. Conclusion: The efficacy of concomitant use of an IM with UST as an induction therapy for CD was significantly superior to that of monotherapy with UST.